ANALISIS HARGA SAHAM DIDETERMINASI PROFITABILITAS, LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS - Dini Ayu Pramitasari (Jurnal Akuntansi dan Keuangan (JAK), 2024)
This study aims to determine the analysis of stock prices determined by Profitability, Liquidity, Solvency and Activity. In companies incorporated in LQ-45 listed on the IDX from 2018 to 2021. A quantitative approach is used in this research method. The population and research sample used LQ-45 companies listed on the IDX in 2018-2021. The data analysis used in this study used classical assumption test and multiple linear regression analysis, hypothesis testing using SPSS version 26 application. The results of this study show that profitability has a positive and significant influence on stock prices. Liquidity and activity have a negative and insignificant effect. Solvency has a positive and insignificant effect on stock prices. Together, Profitability, Liquidity, Solvency and Activity have no effect and are not significant on stock prices in the 2018-2021 period. The results of this study can help investors as policy makers related to Profitability, Liquidity, Solvency and Activity on Stock Prices. The implications of this study provide evidence on stock price analysis determined by Profitability, Liquidity, Solvency and Activity in a company.